Atlantic salmon, Salmo salar, utilizes wax ester-rich oil from Calanus finmarchicus effectively - Olsen, Rolf E; Henderson, R James; Suontama, Jorma; Hemre, Gro Ingunn; Ringo, Einar; Melle, Webjorn; Tocher, Douglas R (Aquaculture, 2004)
Against a background of decreasing availability of fish oils for use in aquaculture, the present study was undertaken to examine whether a wax ester – rich oil derived from the calanoid copepod Calanus finmarchicus, could be used effectively by Atlantic salmon when supplied in their diet. Individually tagged Atlantic salmon of initial weight around 500g were divided into replicate tanks of two dietary groups and fed either a fish oil supplemented diet, or an experimental diet coated with Calanus oil. Wax esters accounted for 37.5% of the lipids in the Calanus oil diet but were absent from the fish oil diet in which triacylglycerols (TAG) were the major lipid class. Over the feeding period (140 days) the salmon fed fish oil displayed a greater increase in length, but there was no significant difference between the two groups in weight gained. The specific growth rates (0.75) and the feed conversion ratio of fish fed the two diets were similar throughout the study. No differences were observed in the apparent digestibility coefficients (ADC) of fish fed Calanus oil or fish oil. The ADC of fatty acids decreased with chain length and increased with unsaturation. Long-chain alcohol utilization showed a similar tendency although there was a notable difference in that saturated long-chain alcohols were utilized better than the comparable fatty acid homologue. In fecal lipid of fish fed Calanus oil, the content of 16:0 alcohol decreased in both the free long-chain alcohol and wax ester fractions, while the corresponding fatty acid increased in the feces of both dietary groups of fish. In contrast, the proportion of the 22:1n-11 alcohol increased in both fecal wax esters and free long-chain alcohol fractions whereas 22:1n-11 fatty acid displayed no accumulation. The observed patterns of fatty acid and long-chain alcohol compositions in fecal lipid compared to those of the initial dietary lipid are consistent with the digestive lipases of salmon preferentially hydrolyzing esters containing PUFA moieties. The wax esters of ...